2022
DOI: 10.1002/dvdy.516
|View full text |Cite
|
Sign up to set email alerts
|

The many roles of dystroglycan in nervous system development and function

Abstract: The glycoprotein dystroglycan was first identified in muscle, where it functions as part of the dystrophin glycoprotein complex to connect the extracellular matrix to the actin cytoskeleton. Mutations in genes involved in the glycosylation of dystroglycan cause a form of congenital muscular dystrophy termed dystroglycanopathy. In addition to its well-defined role in regulating muscle integrity, dystroglycan is essential for proper central and peripheral nervous system development. Patients with dystroglycanopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 174 publications
0
14
0
Order By: Relevance
“…HepaCAM also interacts with aquaporin 4/AQP4, Trpv4 and other components of the DGC in astrocytes, which also includes the intracellular adapter proteins α-dystrobrevin and dystrophin, α/β-dystroglycan transmembrane proteins, and ECM proteins such as agrin and laminin (9). The DGC complex is enriched at the astrocyte–blood vessel interface and has important but understudied roles in regulating BBB development and integrity (44). Functions for hepaCAM in the DGC of GBM cells remains largely unknown and will be an important area of future investigation.…”
Section: Discussionmentioning
confidence: 99%
“…HepaCAM also interacts with aquaporin 4/AQP4, Trpv4 and other components of the DGC in astrocytes, which also includes the intracellular adapter proteins α-dystrobrevin and dystrophin, α/β-dystroglycan transmembrane proteins, and ECM proteins such as agrin and laminin (9). The DGC complex is enriched at the astrocyte–blood vessel interface and has important but understudied roles in regulating BBB development and integrity (44). Functions for hepaCAM in the DGC of GBM cells remains largely unknown and will be an important area of future investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The high expression of aquaporin 4 water channels (AQP4) has been identified in astrocytes, indicating that these cells play a major role in water homeostasis and the clearance of waste substances from the brain interstitial space [78]. The dystroglycan-dystrophin complex is also expressed and localized in the astrocyte end-feet that connect the end-feet cytoskeleton to the basement membrane [79,80]. It is concluded that this complex facilitates the localization of AQP4 in the perivascular space to maintain water flow and form a part of the glymphatic system [80].…”
Section: Blood-brain Barrier Structure and Transportation Systemsmentioning
confidence: 99%
“…The most commonly mutated genes in MDDGA1 are POMT1, POMT2, and POMGNT1. 26,43,50 MDDGB1 is another category of DGPs of moderate severity, including CMD with or without brain structural disorder and developmental delay. MDDGC1 or LGMD-2I is an autosomal recessive disorder characterized by lateonset muscle weakness, with or without ID, but without structural brain abnormalities.…”
Section: Lama2-rd Cmd (Cmd With α2-laminin (Merosin) Deficiency Meros...mentioning
confidence: 99%